Pengaruh Variasi Sandwich Panel Struktur Honeycomb dan Banana Tree Trunks Menggunakan Board Paper Diperkuat Polmeric Foam Terhadap Kekuatan Mekanik - Muhammad Eza Firmansyah; Rizal Hanifi; Iman Dirja (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This research uses board paper as the main material for the sandwich panel structure, which is filled with polymeric foam in the sandwich panel, which will then be subjected to mechanical testing, namely bending and compression, to determine the strength of the sandwich panel structure. The test results according to the ASTM C393 M-16 standard show that the bending strength for the honeycomb shape is 11.93 kN, while for the banana tree trunk core shape the bending strength value is 12.34 (kN). Based on the results of the compression test according to the ASTM C365 M-16 standard. The compressive stress strength value obtained was 6,009 N/mm2 for the honeycomb core shape and for the banana tree trunks core shape, the compressive stress strength value was 7,356 N/mm2. It is necessary to use strengthening methods that are stronger and resistant to delamination and shifting on the strength and durability of the material.